Modelo de comunidad saludable en el sector Vista Alegre, La Libertad - Flores Pérez, Yoya Betzabé (2018)
ABSTRACT The purpose of this report is to analyze how the health promotion model has been applied in the perspective of achieving a healthy community in the Vista Alegre Sector of the Víctor Larco District, understanding the work in each of the family, community and community scenarios. , educational institution, work center and local government and how it affects the changes in lifestyles of the population, giving a social approach to health problems. The health promotion model is operationalized through the Territorial Management program, having indicators of measurement by setting, but lacking a culture of prevention based on education and awareness in the social aspects of coexistence relations, community empowerment and the skills for life, being a key tool to obtain a better result in the promotion of health. The present investigation is of descriptive type with transversal correlational design that describes the relation of the model variables of health promotion and healthy community in a determined moment, using the ethnographic, inductive - deductive, statistical, ethnological methods. The present investigation had 346 people over 18 years of age from Sector Vista Alegre, to whom a questionnaire, observation guide, interview guide, focus groups were applied to analyze how their family relationships were, how they develop community empowerment. and how to use life skills. The results of this research show that the social approach to health problems is essential to achieve an adequate awareness of these and improve the lifestyles of people. Therefore, this research is of vital importance, which allowed to give a scope on how you can achieve better results in the promotion of health and especially Social Work